Pendapatan Sopir Angkot Trayek Pasar Raya-Lubuk Buaya Selama Pandemi Covid-19 - Amalia Sukma; Zul Asri (Jurusan Sejarah FIS UNP, 2022)
This study aims to analyze the development of the Pasar Raya-Lubuk Buaya public transportation route during the Covid-19 Pandemic. The aims of this study were (1) to determine the development of the Pasar Raya-Lubuk Buaya public transportation route during the COVID-19 Pandemic (2) To determine the income of the Pasar Raya-Lubuk Buaya public transportation driver during the COVID-19 pandemic. The type of research used is the historical method. The writing techniques used are heuristics, source criticism, interpretation and historiography. The results show that the number of angkot on the Pasar Raya-Lubuk Buaya route did not decrease during the Covid-19 pandemic, which amounted to 25 fleets, but the income of angkot drivers decreased during covid 19. This is because angkot reduces the number of trips due to quiet passengers.